Photovoltaic Flyback Microinverter With Tertiary Winding Current Sensing - Za'im, Radin; Jamaludin, Jafferi; Rahim, Nasrudin Abd (Institute of Electrical and Electronics Engineers, 2019)
This paper presents a new low cost, non-invasive, and isolated current sensing technique for the grid-tied photovoltaic (PV) flyback microinverter. This is accomplished by using the flyback transformer itself as a current sensor, achieved by introducing a tertiary winding to the flyback transformer. The mathematical integration of the tertiary winding's open circuit voltage through a ground-clamped-integrator results in the sensing of the magnetizing current. Since the magnetizing current is a combination of both primary and secondary current, control of both grid current and maximum power point tracking (MPPT) is implemented by sensing only the magnetizing current. This allows the PV, primary, secondary, and the grid current loops to be free of any invasive current sensors. Moreover, controlling the magnetizing current provides an alternative solution to an inherent problem with continuous conduction mode (CCM), the control complexity. Linear ramping and de-ramping of the magnetizing current allows for a set-reset hysteresis control to be implemented, resulting in CCM control simplicity that is akin to the boundary and discontinuous conduction mode. A grid-tied microinverter prototype is presented for verification, achieving the following experimental result: 1.9% grid current THD, 0.9988 power factor, above 99% static MPPT efficiency and dynamic efficiency of 98.50%.